Shaping Children's Character Through Religious and Family Education - Arbain Maimunah; Dinda Mayang Sari; Ahmad Nur Choliq; Sukatin Sukatin; Muhammad Yusup (CV. Rayyan Dwi Bharata, 2022)
Islamic Religious Education (PAI) is one of the most importances pilar of character education. Character education will build well, if it is started from cultivating religious sense of students, therefore, PAI lesson become one of supporting lesson of character education Through PAI teaching and learning, the students is taught belief of God as the basic of their religion, taught al quran and hadits as their way of life, taught fiqih as law signs in doing Islam teaching, taught Islam history as a good life example, and taught ethica as the way of human character. The Role of Parents in Improving The Character of child Education in The Family. Parents play an important role to develop their potential. parents are educators first and foremost in a family environment, parents need to be aware that the child has great potential at birth.